2002
DOI: 10.1086/342370
|View full text |Cite
|
Sign up to set email alerts
|

Halting Planet Migration in the Evacuated Centers of Protoplanetary Disks

Abstract: Precise Doppler searches for extrasolar planets find a surfeit of planets with orbital periods of 3-4 days and no planets with orbital periods less than 3 days. The circumstellar distance , where small grains in a proto-R 0 planetary disk reach sublimation temperatures (∼1500 K), corresponds to a period of ∼6 days. Interior to , R 0 turbulent accretion due to magnetorotational instability may evacuate the disk center. We suggest that planets with orbital periods of 3-4 days are so common because migrating plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 38 publications
(48 reference statements)
4
63
2
Order By: Relevance
“…They found that all bodies migrated until reaching a point slightly exterior to the cavity edge, where they were effectively trapped in a stable configuration in almost circular orbits. Although this result appears different from that predicted by Kuchner & Lecar (2002), each is valid, as we shall see, for a different range of planetary masses.…”
Section: Introductioncontrasting
confidence: 96%
See 2 more Smart Citations
“…They found that all bodies migrated until reaching a point slightly exterior to the cavity edge, where they were effectively trapped in a stable configuration in almost circular orbits. Although this result appears different from that predicted by Kuchner & Lecar (2002), each is valid, as we shall see, for a different range of planetary masses.…”
Section: Introductioncontrasting
confidence: 96%
“…Since it is unclear whether in-situ formation occurs, the current orbital and physical characteristics of these planets provide important constraints on their past evolution and formation process. Several mechanisms have been proposed to explain the pile-up of hot planets with a three-day orbital period, including a truncation of the gaseous disk by the star (Lin et al 1996;Kuchner & Lecar 2002), planetary scattering combined with Kozai resonance and tidal circularization (Nagasawa et al 2008), planetary evaporation (Davis & Wheatly 2009), and tidal interactions with the parent star (Jackson et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some effects that may be influencing the observed sizes include additional sources of luminosity (Hillenbrand et al 1992;Hartmann et al 1993), photoevaporation (Hollenbach et al 1994;Danchi et al 2001), turbulent accretion (Kuchner & Lecar 2002), or more complicated emission morphology (scattered light, viewing angles, disk plus envelope combinations, etc. ; Miroshnichenko et al 1999).…”
Section: Other Important Effectsmentioning
confidence: 99%
“…The inward migration of a planet could be stopped near the star as a result of tidal interaction with the host star, or through the evacuation of the inner disk by some processes such as interactions with stellar magnetosphere (Lin, Bodenheimer & Richardson 1996), magnetorotational instability (Kuchner & Lecar 2002), photoevaporation by irradiation from the central star (Matsuyama, Johnstone and Murray 2003), etc. The negligible Planet system dynamics 33 eccentricity of all extra-solar planets with periods less than 6 days can be accounted for by tidal dissipation induced by their host stars.…”
Section: Problems On Planet Migrationmentioning
confidence: 99%